Evaluating transfer programs within a general equilibrium framework - Coady, David; Harris, Rebecca Lee (International Food Policy Research Institute, 2001)
The authors set out a general equilibrium model for the evaluation of a domestically financed transfer program, which helps to combine the results from a computable general equilibrium model with disaggregated household data.Using a Mexican cash transfer program as an illustration, they use the approach to show that the substantial welfare gains that result from the switch from universal food subsidies to targeted cash transfers reflect both the improved targeting efficiency of the latter as well as a relaxation of the trade-off between equity and efficiency objectives when designing tax systems.